Stopniowanie trudności w nauczaniu religii inspirowane nowymi założeniami programowymi - Zellma, Anna (Poznańskie Studia Teologiczne, 2011)
Gradation of difficulty is one of the fundamental didactic principles in religious instruction. This principle determines the norms for religion teachers’ activities as far as conveying knowledge and developing students’ skills in an accessible way adequate to their level of development is concerned. The aim of this paper is to present the principle of gradation of difficulty as seen by the authors of new curricula for religious instruction at schools, which was approved in 2010. Consequently, the article begins with a description of the general understanding of the difficulty gradation principle in religious instruction as defined by contemporary methodologists. The next section presents how the issue is perceived by the authors of the amended „Core curriculum of catechesis of the Catholic Church in Poland” and „Curriculum of Roman-Catholic religious instruction in kindergartens and schools” prepared in connection with the former document. Final remarks contain, apart from conclusions and catechetic suggestions, specific guidelines for authors of new series of textbooks and religious instruction materials for various student groups.